A aplicação da lei de responsabilidade fiscal no executivo municipal dos Estados brasileiros: Despesas com pessoal e restos a pagar - Vieira, Ednaldo Rogerio Tenorio (2022)
With this scientific article it is proposed to observe the interferences of the Law of Fiscal Responsibility on the public accounts of the municipal executive. looking for the best understanding of the necessary requirements to comply with the limits and prohibitions that municipalities must comply with the publication of this law. Through bibliographic research and documents, the objective is to demonstrate compliance with the LRF by municipal managers; adequacy according to the new limitations on indebtedness and public debt and the issue of inspection of these actions, through transparency portals and other channels. Understanding the prescriptions of this law makes municipal public accounts a factor of paramount importance for the country's financial health, as the proper adequacy of the limits to be expenses, mainly with personnel expenses, means that public entities are able to invest in the areas of its competence and regulation